New Role for Photoexcited Na2 Eosin Y via the Direct Hydrogen Atom Transfer Process in Photochemical Visible-Light-Induced Synthesis of 2-Amino-4H-Chromene Scaffolds Under Air Atmosphere - Mohamadpour, Farzaneh (Frontiers in Chemistry, 2022)
The Knoevenagel-Michael cyclocondensation of malononitrile, aryl aldehydes, and resorcinol was used as a multicomponent green tandem strategy for the metal-free synthesis of 2-amino-4H-chromene scaffolds. Through a visible-light-induced process, the photo-excited state functions derived from Na2 eosin Y were used as direct hydrogen atom transfer catalysts in aqueous ethanol at ambient temperature. The purpose of this study is to examine the further use of an organic dye that does not contain metal, is inexpensive and commercially available. Na2 eosin Y is synthesised by photochemical means using the least amount of catalyst, which results in excellent yields, energy efficiency, and environmental friendliness, high atom economy, time-saving features, and ease of operation.As a result, some properties of green and sustainable chemistry are met. This kind of cyclization can be performed on a gram scale, indicating the potential utility of this reaction in industry.